Estudo do papel da ADAM9 na disseminação tumoral via sistema linfático: possível alvo farmacológico - Micocci, Kelli Cristina (2014)
Tumor spreading occurs mainly by two pathways: through blood vessels and by lymphatic vessels, but the last is preferred by breast tumor cells. Some proteins are involved in cell adhesion and proteolysis, causing metastasis, such as ADAMs, a family of multi-domain and multi- functional proteins that contribute in these processes. ADAM9, a member of this family, has been increased in a large number of human carcinomas, including, breast cancer. In this context, the aim of this study was to evaluate the role of ADAM9 in tumor spreading via blood and lymphatic systems, in the search for new targets and focusing the development of new therapeutical tools. Therefore, MDA-MB-231 breast tumor cells were silenced for ADAM9 and tested with respect to their adhesive and invasive activity against blood and lymphatic endothelium. Our results showed that ADAM9 silencing in MDA-MB-231 breast cancer cells inhibited the invasion of this cells in matrigel (71.51 ± 8.02%) when compared to control cells, without affecting cell adhesion, proliferation, migration, and gene expression of the ADAM10, ADAM12, ADAM-17, cMyc, MMP9, VEGF-A, VEGF-C, Osteopontin and Collagen XVII, however, there was a decrease in the expression of the ADAM15 and increased expression of MMP2 when compared to controls. Furthermore, ADAM9 silencing did not affect the adhesion under flow to these vascular endothelial cells (HMEC-1 and HUVEC) and lymphatic (HMVEC-dLyNeo-Der). However, there was a decrease in the rate of trans-endothelial migration through the monolayer endothelial cells (HUVEC, HMEC-1 and HMVEC-dLyNeo-Der) by approximately 50%, 40% and 32%, respectively. In conclusion, ADAM9 showed to be essential in invasion and extravasation of MDA-MB-231 breast cancer cells through the blood and lymphatic vessels in vitro.